グラム染色が診断に有効であった顎関節偽痛風の1例 - 鵜澤, 成一; 永川, 賢治; 太田, 嘉幸; 桝井, 敦史 (日本口腔外科学会雑誌, 2019)
Pseudogout is acute arthritis caused by calcium pyrophosphate dehydrate (CPPD). We report a case of pseudogout in the temporomandibular joint (TMJ) that was effectively diagnosed on Gram staining.　A 79-year-old woman was referred to our hospital because of swelling and pain in a left temporomandibular lesion. Clinical and blood test findings suggested acute suppurative arthritis of the TMJ. The patient was treated with antibiotics after arthrocentesis. Bacteria was not detected on Gram staining of joint fluid, but crystal components were comfirmed. Pseudogout was diagnosed on the basis of multiple small regions of mineralization and imaging and crystal characteristics under a polarizing microscope. Symptoms were improved by nonsteroidal anti-inflammatory drugs (NSAIDs) after the cessation of antibiotics. Gram staining was a simple and quick technique that facilitated the diagnosis of temporomandibular pseudogout.